2008
DOI: 10.1111/j.1600-051x.2008.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms in periodontal disease: a meta‐analysis of 53 studies including 4178 cases and 4590 controls

Abstract: Using random effect methods we found statistically significant association of IL-1A C[-889]T and IL-1B C[3953/4]T polymorphisms with chronic periodontal disease without any evidence of publication bias or significant statistical heterogeneity. A weak positive association was also found concerning IL-1B T[-511]C and chronic periodontal disease. No association was found for all the cytokines examined as far as the aggressive form of the disease is concerned. Future studies may contribute to the investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 103 publications
(142 reference statements)
9
150
0
12
Order By: Relevance
“…A recent study also reviewed the association between the IL-6 −174 G/C polymorphism and periodontitis (Nikolopoulos et al, 2008). It is difficult to compare their results directly with ours for three reasons.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study also reviewed the association between the IL-6 −174 G/C polymorphism and periodontitis (Nikolopoulos et al, 2008). It is difficult to compare their results directly with ours for three reasons.…”
Section: Discussionmentioning
confidence: 79%
“…Among the principal genetic variants pointed out from literature, 2,46 for the present study, we decided to focus our attention on the 28 candidate gene polymorphisms, located within 14 different genes, described in Table 2, and to investigate their relation with AgP susceptibility.…”
Section: Genotyping and Snps Selectionmentioning
confidence: 99%
“…6 Interleukin (IL)-6 is a pleiotropic cytokine released by many cell types, and its secretion levels are determined by the producing cell type and the genetic background of the source cells. 8 Among several kinds of cytokines, IL-6 was found to be increased in gingival crevicular fluid (GCF) and gingival tissues of patients with periodontal disease. 9 A recent study reported that chronic periodontitis(CP) and generalized aggressive periodontitis (GAgP) patients had significantly higher GCF IL-6 levels in comparison with the healthy subjects.…”
Section: Introductionmentioning
confidence: 99%